DNAN behaviour during laboratory-scale explosiveness test - Galante, Erick; Mai, Nathalie; Ladyman, Melissa K.; Gill, Philip P.; Temple, Tracey (Cranfield University, 2018)
Video recorded during a laboratory-scaled explosiveness test, in which a 10mg sample of DNAN was heated (43ºC/min) within a sealed 10mL headspace vial
Keywords: 'laboratory-scaled explosiveness test'; 'DNAN'; 'Chemical Characterisation of Materials'